Strategies to facilitate integrated care for people with alcohol and other drug problems: a systematic review - Michael Savic; David Best; Victoria Manning; Dan I. Lubman (BMC, 2017)
Abstract Background There is a growing body of research highlighting the potential benefits of integrated care as a way of addressing the needs of people with alcohol and other drug (AOD) problems, given the broad range of other issues clients often experience. However, there has been little academic attention on the strategies that treatment systems, agencies and clinicians could implement to facilitate integrated care. Methods We synthesised the existing evidence on strategies to improve integrated care in an AOD treatment context by conducting a systematic review of the literature. We searched major academic databases for peer-reviewed articles that evaluated strategies that contribute to integrated care in an AOD context between 1990 and 2014. Over 2600 articles were identified, of which 14 met the study inclusion criteria of reporting on an empirical study to evaluate the implementation of integrated care strategies. The types of strategies utilised in included articles were then synthesised. Results We identified a number of interconnected strategies at the funding, organisational, service delivery and clinical levels. Ensuring that integrated care is included within service specifications of commissioning bodies and is adequately funded was found to be critical in effective integration. Cultivating positive inter-agency relationships underpinned and enabled the implementation of most strategies identified. Staff training in identifying and responding to needs beyond clinicians' primary area of expertise was considered important at a service level. However, some studies highlight the need to move beyond discrete training events and towards longer term coaching-type activities focussed on implementation and capacity building. Sharing of client information (subject to informed consent) was critical for most integrated care strategies. Case-management was found to be a particularly good approach to responding to the needs of clients with multiple and complex needs. At the clinical level, screening in areas beyond a clinician's primary area of practice was a common strategy for facilitating referral and integrated care, as was joint care planning. Conclusion Despite considerable limitations and gaps in the literature in terms of the evaluation of integrated care strategies, particularly between AOD services, our review highlights several strategies that could be useful at multiple levels. Given the interconnectedness of integrated care strategies identified, implementation of multi-level strategies rather than single strategies is likely to be preferable.